Organic Psychotic Disorder: A Case Report - Kuloğlu, Murat; Atmaca, Murad; Serhatlıoğlu, Selami; Tezcan, A. Ertan (Fırat University, 2002)
Organic psychotic disorder is a psychiatric picture secon-dary to underlining an organisity and has considerably delusions and hallucinations. Forty years old, male patient; he applied to our clinic because of some complaints such as globus hystericus, palpitation, the fear of death, insomnia, suspiciousness, feeling the voice of wind, headache, feeling visual hallucination as walking an insect on carpet and on his own surface of body, thought of entering his body to a magnetic field and controlled. In mental examination, there were important psychiatric signs such as anticipatory anxiety, depressive mood, insomnia, obsession and compulsions, visual, auditory and tactil hallucinations, persecution and somatic delusions, ambivalance and derealization. On the basis of computerized brain tomography (CT) evaluation, a hipodence structure (posttraumatic porencephaly) in left parieto-occipital area was detected and the patients was diagnosed with organic psychotic disorder. Our case emphasizes the importance of organisity in the development of organic psychotic disorder.

Organik psikotik bozukluk, altta yatan özgün bir organisiteye ikincil olarak gelişen, varsanı ve sanrıların belirgin olarak görüldüğü bir psikiyatrik tablodur. 40 yaşında erkek hasta, kliniğimize göğsünde sıkışma hissi, çarpıntı, ölüm korkusu, uykusuzluk, şüphecilik, rüzgar sesi duyma, sağ elini kullanamama, baş ağrısı, halı üzerinde ve vücudunda böcek yürüyor gibi görme, vücudunun bir manyetik alana girdiği ve yönlendirildiği yakınmalarıyla başvurdu. Ruhsal durum muayenesinde; yoğun beklenti anksiyetesi, depresif duygulanım, insomnia, obsesyon ve kompulsiyonlar, görsel, işitsel, dokunsal varsanılar, perseküsyon ve somatik sanrılar, ambivalans ve derealizasyon mevcuttu. Bilgisayarlı Beyin Tomografisi (BBT) ile sol parieto-oksipital bölge düzeyinde hipodens bir oluşum (posttravmatik porensefali) tesbit edilen hastaya organik psikotik bozukluk tanısı konuldu. Olgumuz; psikotik bulguların oluşumunda, organik temelin önemini belirgin şekilde vurgulaması açısından çarpıcıdır.
ORGANİK PSİKOTİK BOZUKLUK OLGU SUNUMU